2000
DOI: 10.1103/physrevb.62.15287
|View full text |Cite
|
Sign up to set email alerts
|

Universal features of self-trapping in nonlinear tight-binding lattices

Abstract: We show that nonlinear tight-binding lattices of different geometries and dimensionalities, display an universal selftrapping behavior. First, we consider the single nonlinear impurity problem in various tight-binding lattices, and use the Green's function formalism for an exact calculation of the minimum nonlinearity strength to form a stationary bound state. For all lattices, we find that this critical nonlinearity parameter (scaled by the energy of the bound state), in terms of the nonlinearity exponent, fa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
(18 reference statements)
0
13
0
Order By: Relevance
“…We should keep in mind that these transitions may occur and be observed in real physical systems, where an estimation range is more relevant [1][2][3][4]). In fact, if we use another quantity as an indicator (for instance, the space-averaged fraction of power [15]), we observe the occurrence of the self-trapping transition in similar regions. …”
Section: B Dynamical Tongue and Self-trapping Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…We should keep in mind that these transitions may occur and be observed in real physical systems, where an estimation range is more relevant [1][2][3][4]). In fact, if we use another quantity as an indicator (for instance, the space-averaged fraction of power [15]), we observe the occurrence of the self-trapping transition in similar regions. …”
Section: B Dynamical Tongue and Self-trapping Transitionmentioning
confidence: 99%
“…A first attempt to find a more general criterion was done in Ref. [15] by comparing γ c with the minimum bound-state energy of a nonlinear impurity problem. They found that, for nonlinear lattices of different dimensions and topologies, there is a kind of universal ratio of ≈ 1.3 between these two energies.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, one sometimes studies the 1D DNLS equation with larger hoping to capture the main effects of higher dimensionality in a simpler 1D model (e.g., Refs. [21][22][23][24]). Recently [25], similar arguments were also used in the study of a 1D KG chain with a 8 on-site potential, to mimic the effects of an excitation threshold for breathers in the thermalization dynamics of a three-dimensional KG lattice.…”
Section: Introductionmentioning
confidence: 99%
“…Bound states for single nonlinear impurities embedded in infinite lattices include chains [10,11,12], Cayley trees [14], triangular [16] and a cubic [15,16] lattices. Now, since the creation of a bound state, or the dynamical selftraping at the impurity site implies the localization of energy on a scale of the order of the lattice spacing, one might surmise that, by placing the nonlinear impurity at or near the surface of a semi-infinite lattice, the nonlinearity strength needed to effect localization would decrease, facilitating in this way its creation and experimental observation.…”
mentioning
confidence: 99%